Différences de gestion collective des situations critiques dans les activités de service selon deux types d’organisation du travail - Sandrine Caroly (Perspectives Interdisciplinaires sur le Travail et la Santé)
The objective of the research was to help service sector employees to identify the collective regulation used in the daily management of service relations, in order to counteract the resulting fluctuations and problems. In theory, collective regulation depends on different forms of collective work, the preparation of group rules and the implementation limitations imposed by the age and experience of the workers concerned. For the study the work of the clerks in two post offices was analyzed. The two sites differed in terms of organization of work and staff stability.The purpose of the analysis was to compare collective regulation of « critical situations » by employees according to the type of wicket organization (division of work or tolerance/encouragement of group activities). The « critical situations » in the service relationship were the result of « conflicting goals » due to personal conceptions of the employees’ public service mission, structural working regulations, expectations and customer diversity. The comparison of the two types of collective management revealed job overlaps with possibilities for discretion and autonomy, thus saving time when dealing with customers and improving effectiveness when transmitting knowledge and solving problems. The results will be useful for improving existing tools and training themes, and for recognizing the complexity of the work involved in different service activities.